(untitled) (Південний архів (історичні науки), 2026)
This article examines the process of shaping the policy of glasnost (transparency) in the Kyiv region during the period of “perestroika” (perebudova); analyzes the factors that influenced its development; and identifies the characteristic features, peculiarities, and consequences of glasnost’s development in the region. The aim of the study is a comprehensive scientific analysis of the tasks and goals that the Soviet authorities set for themselves when implementing the policy of glasnost, as well as society’s reaction to these changes. The methodological basis of the study consists of the general scientific principles of historicism and objectivity, as well as retrospective, comparative-historical, and analytical approaches. The principle of historicism allows us to examine the process of glasnost in the Kyiv region within the context of the prevailing historical circumstances, namely the policy of “perestroika” under the leadership of M. Gorbachev. The principle of objectivity reveals to us the true picture of the highly contradictory and complex circumstances of the second half of the 1980s. in which the Ukrainian SSR, and specifically the Kyiv Oblast, found themselves. The retrospective method allows us to extrapolate the process of expanding freedom of speech and government communication, along with its challenges, onto contemporary sociopolitical trends. The comparative-historical method reveals the distinctive features and characteristics of the glasnost policy in the Kyiv Oblast and other regions of Ukraine. The analytical method allows us to identify the causes and factors that influenced glasnost in the Kyiv region. Scientific novelty. The policy of glasnost, as a component of the perestroika policy initiated by M. Gorbachev, is highly relevant and has been covered in the works of a considerable number of scholars in more general terms. However, the regional specifics of this process remain insufficiently studied. Therefore, the study of the policy of glasnost in the Kyiv region under perestroika is highly relevant and of significant scientific interest. Results and Conclusions. The characteristic features and specific aspects of the implementation of the policy of glasnost in the Kyiv region during the period of perestroika included, on the one hand, traditional measures that were in line with all-Union and republican initiatives: establishing communication channels between the authorities and the public through the organization of “round tables,” “hotlines,” open-house days, informal meetings within work collectives; conducting various types of surveys to gauge public sentiment and opinion; implementing and/or simulating changes in the openness of party and state structures; strengthening the role of the press to increase public awareness and reduce the information vacuum; and expanding and deepening the process of rehabilitation, etc. On the other hand, the implementation of the policy of glasnost in the Kyiv region had its own peculiarities, which were due to the fact that the Kyiv region, as a region close to the capital of the Ukrainian SSR, had the opportunity to accelerate, in the context of social-political processes due to the high concentration of elites, including opposition figures, while simultaneously hindering them because of their proximity to the decision-making center at the republican level, where conservative figures constantly sought to slow the pace of social transformation. A specific factor influencing the development of glasnost in the region was the Chernobyl tragedy, which effectively became a kind of litmus test – for a long time, silence and disinformation served as the framework for information about the accident. As a result, the energy disaster quickly transformed from an environmental factor in public life into a powerful political one. Furthermore, during the implementation of glasnost policies, the Kyiv region was characterized by territorial heterogeneity and a variety of models for permissible actions in the information sphere – ranging from the liberal capital to the restrictive provincial – which significantly limited full freedom of speech.